Alteration of forest succession and carbon cycling under elevated CO2. (18th November 2015) - Miller, Adam D.; Dietze, Michael C.; DeLucia, Evan H.; Anderson‐Teixeira, Kristina J.
Abstract: Regenerating forests influence the global carbon (C) cycle, and understanding how climate change will affect patterns of regeneration and C storage is necessary to predict the rate of atmospheric carbon dioxide (CO2 ) increase in future decades. While experimental elevation of CO2 has revealed that young forests respond with increased productivity, there remains considerable uncertainty as to how the long‐term dynamics of forest regrowth are shaped by elevated CO2 (eCO2 ). Here, we use the mechanistic size‐ and age‐ structured Ecosystem Demography model to investigate the effects of CO2 enrichment on forest regeneration, using data from the Duke Forest Free‐Air Carbon dioxide Enrichment (FACE) experiment, a forest chronosequence, and an eddy‐covariance tower for model parameterization and evaluation. We find that the dynamics of forest regeneration are accelerated, and stands consistently hit a variety of developmental benchmarks earlier under eCO2 . Because responses to eCO2 varied by plant functional type, successional pathways, and mature forest composition differed under eCO2, with mid‐ and late‐successional hardwood functional types experiencing greater increases in biomass compared to early‐successional functional types and the pine canopy. Over the simulation period, eCO2 led to an increase in total ecosystem C storage of 9.7 Mg C ha ‐1 . Model predictions of mature forest biomass and ecosystem–atmosphere exchange of CO2 and H2 O were sensitive to assumptions about nitrogen limitation; both the magnitude and persistence of the ecosystem response to eCO2 were reduced under N limitation. In summary, our simulations demonstrate that eCO2 can result in a general acceleration of forest regeneration while altering the course of successional change and having a lasting impact on forest ecosystems.